Cryo-EM Structure of a Kinetically Trapped Dodecameric Portal Protein from the Pseudomonas-phage PaP3. Issue 9 (15th May 2022) - David Hou, Chun-Feng; Swanson, Nicholas A.; Li, Fenglin; Yang, Ruoyu; Lokareddy, Ravi K.; Cingolani, Gino
Graphical abstract: Highlights: First cryo-EM structure of a Pseudomonas -phage portal protein. Naïve PaP3 portal protein assembles into a helical quaternary structure. The C-terminal portal barrel controls quaternary structure assembly. Profund asymmetry of portal rings built by a different number of subunits. Tunnel loops generate a restriction in the DNA channel. Abstract: Portal proteins are dodecameric assemblies that occupy a unique 5-fold vertex of the icosahedral capsid of tailed bacteriophages and herpesviruses. The portal vertex interrupts the icosahedral symmetry, and in vivo, its assembly and incorporation in procapsid are controlled by the scaffolding protein. Ectopically expressed portal oligomers are polymorphic in solution, and portal rings built by a different number of subunits have been documented in the literature. In this paper, we describe the cryo-EM structure of the portal protein from the Pseudomonas- phage PaP3, which we determined at 3.4 Å resolution. Structural analysis revealed a dodecamer with helical rather than rotational symmetry, which we hypothesize is kinetically trapped. The helical assembly was stabilized by local mispairing of portal subunits caused by the slippage of crown and barrel helices that move like a lever with respect to the portal body. Removing the C-terminal barrel promoted assembly of undecameric and dodecameric rings with quasi -rotational symmetry, suggesting that the barrel contributes to subunits mispairing. However, ΔC-portal rings were intrinsically asymmetric, with most particles having one open portal subunit interface. Together, these data expand the structural repertoire of viral portal proteins to Pseudomonas -phages and shed light on the unexpected plasticity of the portal protein quaternary structure.